Pengaruh Model Pembelajaran Discovery Learning terhadap Hasil Belajar Siswa SMP Pada Mata Pelajaran PAI - Miftahur Rohmah; Didit Darmawan (Universitas Batanghari Jambi, 2026)
The decline in students’ learning outcomes in Islamic Religious Education has prompted various innovations in instructional models. This study aims to examine the effect of the Discovery Learning model on students’ learning outcomes. The method employed is a literature review with a qualitative approach, analyzing relevant recent journal articles and undergraduate theses. The findings indicate that the implementation of the Discovery Learning model in Islamic Religious Education involves several stages, including stimulation, problem identification, data collection, data processing, verification, and drawing conclusions. Through these stages, the Discovery Learning model has been shown to improve students’ learning outcomes. The implications of this study suggest the need for curriculum development that integrates the Discovery Learning model, as well as teacher training to support the use of innovative instructional approaches